2020
DOI: 10.1016/j.ctrv.2020.102104
|View full text |Cite
|
Sign up to set email alerts
|

The optimal timing for the interval to surgery after short course preoperative radiotherapy (5 ×5 Gy) in rectal cancer - are we too eager for surgery?

Abstract: Background:The improved overall survival (OS) after short course preoperative radiotherapy (SCPRT) using 5 × 5 Gy reported in the early rectal cancer trials could not be replicated in subsequent phase III trials. This original survival advantage is attributed to poor quality of surgery and the large differential in local recurrence rates, with and without SCPRT. Immuno-modulation during and after SCPRT and its clinical implications have been poorly investigated. We propose an alternative explanation for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 109 publications
1
11
0
Order By: Relevance
“…Furthermore, we have shown that acute RT (SRT) affects the presence of T-cyt and T-helper cell populations the most. Strikingly, this is less evident with LRT, suggesting repopulation takes place in the interval that distinguishes SRT and LRT, which is in line with previous models (4,24,30). Previously, Mezheyeuski (17) has shown that memory T-helper, memory T-cyt cells, and macrophage counts decreased immediately after radiotherapy and were increased after longer treatment intervals.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we have shown that acute RT (SRT) affects the presence of T-cyt and T-helper cell populations the most. Strikingly, this is less evident with LRT, suggesting repopulation takes place in the interval that distinguishes SRT and LRT, which is in line with previous models (4,24,30). Previously, Mezheyeuski (17) has shown that memory T-helper, memory T-cyt cells, and macrophage counts decreased immediately after radiotherapy and were increased after longer treatment intervals.…”
Section: Discussionsupporting
confidence: 91%
“…A time interval of at least 7 days after SCRT has been reported to be probably required to achieve a favorable immune response, suggesting that the choice of the timing of immunotherapy after SCRT is important. 35 The PACIFIC trial reported that the initiation of durvalumab within 2 weeks after chemoradiotherapy (rather than ≥2 weeks) was linked to a higher clinical benefit. 36 Therefore, we have reasons to believe that our choice of timing for the initiation of immune checkpoint inhibitor camrelizumab in this study (median 12 days) is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Through activation of cytotoxic T cells, remaining vital tumour cells are directly and indirectly targeted by dendritic, B or T helper cells. To date, the link between the anti‐tumour immune response and tumour regression has focused upon high or low immune infiltrates predicting patient outcome 27,28 . As therapy interplays with the tumour immune landscape, it seems plausible that the immune response could influence the pattern of response.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the link between the anti-tumour immune response and tumour regression has focused upon high or low immune infiltrates predicting patient outcome. 27,28 As therapy interplays with the tumour immune landscape, it seems plausible that the immune response could influence the pattern of response. Further studies on these specific immune cell subsets and their possible link to patterns of response are therefore needed.…”
Section: Discussionmentioning
confidence: 99%